Impressões do tempo: os Almanaques no Ceará (1870-1908) - Macambira, Débora Dias (2010)
The study is about the Almanac, an editorial genre in wide circulation during the nineteenth century, focusing between the years 1870 and 1908 in Ceará. As a source and object of resource, the Almanac connects to the history of books and reading in Brazil, contributing to knowledge about the distribution of printed, forming circles of readings and networks of readers, making even the stimulus for writing for different paths. Combining format, content and language of greater access, these forms have contributed to the formation and expansion of the readership, promoting cultural exchanges in different areas of the provinces, between points in Brazil, Portugal and other countries. Like editorial spaces of experimentation, the Almanacs gradually incorporated the changes promoted by technical innovations, new content and tested ways of telling, keeping always linked to social and cultural needs of timekeeping. The Almanac is also seen reading, prescribing, promoting the book, linking the printed circuits.